Cesarean scar pregnancy: A clinical case report - Slaoui, Aziz; Bennani, Aicha; Tayeb, Roughaya; Zeraidi, Najia; Lakhdar, Amina; Baydada, Aziz; Kharbach, Aicha (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Among the different forms of ectopic pregnancy, cesarean scar pregnancy is one of the most uncommon with an estimated incidence of 1/1800 pregnancies. A major risk of massive hemorrhage, it requires active management as soon as it is diagnosed because it can affect the functional prognosis of the patient (hysterectomy) but can also be life-threatening. Different surgical techniques are generally proposed in first intention to patients who no longer wish to have children, who are hemodynamically unstable and/or in case of failure of medical treatment. Case presentation: We hereby report the case of a young 19-year-old patient with no particular medical history, gravida 2 para 1 with a live child born after a cesarean section for fetal heart rhythm abnormalities during labor 5 months earlier and who presented to the emergency room of our structure for the management of a cesarean pregnancy scar diagnosed at 6 weeks of amenorrhea. She was successfully managed with an intramuscular injection of methotrexate. The follow-up was uneventful. Conclusion: The implantation of a pregnancy on a cesarean section scar is becoming more and more frequent. With consequences that can be dramatic, ranging from hysterectomy to life-threatening hemorrhage, clinicians must be familiar with this pathological entity and be prepared for its management. The latter must be rapid and allow, if necessary, the preservation of the patient’s fertility. In this sense, conservative medical treatment with methotrexate injections should be proposed as a first-line treatment in the absence of contraindication.